Pengaruh Media Macromedia Flash Terhadap Literasi Sains dan Sikap Demokratis Mahasiswa - Lina Nida Zulfa*; Haryanto Haryanto (Universitas Syiah Kuala, 2021)
College students are often considered as adult humans so that when learning science, the use of interesting media is not noticed. Quality science learning can form college students who have scientific literacy and high democratic attitudes which are very important in the 21st century. The solutions that can be used to solve these problems is the macromedia flash learning media. This study aims to determine: 1) the effect of macromedia flash on scientific literacy; 2) the influence of macromedia flash on democratic attitudes; 3) the effect of macromedia flash on scientific literacy and democratic attitudes of college students simultaneously. This study used a quasi experimental method with a nonequivalent control group design. The study population was all PGSD Semester IV students of Ahmad Dahlan University. Sampling with cluster random sampling technique. Data were collected by tests and questionnaires. Analysis of research data using t and manova test. Based on the results of the study obtained both t and manova tests, the significance value is smaller than 0.05, so it can be concluded that: 1) there is an effect of macromedia flash on scientific literacy; 2) there is an effect of macromedia flash on democratic attitudes; 3) there is an effect of macromedia flash on scientific literacy and democratic attitudes of college students simultaneously.